2017
DOI: 10.1371/journal.pone.0187525
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for congruent impairment in micro and macrovascular function in type 1 diabetes

Abstract: Diabetes affects large and small vessels through mechanisms only partially known. In the present study, we evaluated the function of capillaries and large arteries in subjects with type 1 diabetes mellitus (T1DM) to study the effect of chronic hyperglycemia in the absence of other cardiovascular risk factors. Twenty-five subjects with T1DM and 12 healthy age-matched controls were enrolled. Nine patients had mild or moderate retinopathy. Contrast enhanced ultrasound was used to measure perfusion of the deep for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…These findings are in line with a cross‐sectional investigation conducted in a cohort of T1DM patients reporting a strong association between retinopathy and reduced muscle strength and quality of the quadriceps muscles . A recent study has also reported that diabetic retinopathy is characterized by a more severe impairment of skeletal muscle perfusion at rest and after ischemia when compared with uncomplicated T1DM patients . Vascular dysfunction was proposed as the main mechanism underlying the loss of muscle performance in patients with retinopathy …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings are in line with a cross‐sectional investigation conducted in a cohort of T1DM patients reporting a strong association between retinopathy and reduced muscle strength and quality of the quadriceps muscles . A recent study has also reported that diabetic retinopathy is characterized by a more severe impairment of skeletal muscle perfusion at rest and after ischemia when compared with uncomplicated T1DM patients . Vascular dysfunction was proposed as the main mechanism underlying the loss of muscle performance in patients with retinopathy …”
Section: Discussionsupporting
confidence: 85%
“…A recent study has also reported that diabetic retinopathy is characterized by a more severe impairment of skeletal muscle perfusion at rest and after ischemia when compared with uncomplicated T1DM patients . Vascular dysfunction was proposed as the main mechanism underlying the loss of muscle performance in patients with retinopathy …”
Section: Discussionmentioning
confidence: 98%
“…Heightened adrenergic vascular tone along with endothelial dysfunction (3,49,68) and structural remodeling of the microvasculature (25,29,42) contributes to the compromised vasodilatory ability seen in pathological states, such as diabetes mellitus and metabolic syndrome (23,24,44). A commonly used marker of vascular dysfunction is impaired postocclusive reactive hyperemia (PORH) (6,26,27,38,42,49). Frisbee (26) demonstrated in obese Zucker rats, a model of metabolic syndrome, that deteriorated PORH in cremaster muscle arterioles is significantly improved by ␣-adrenoreceptor blockade.…”
Section: Introductionmentioning
confidence: 99%
“…However, Emanuel et al [29] found no correlation of peripheral insulin sensitivity with skeletal muscle MBV at baseline, or with MBV during hyperinsulinemia or with the percent change in MBV. Peripheral insulin sensitivity also did not significantly correlate with MBV during hyperinsulinemia and combined vasodilator (iloprost) infusion, or with the MBV percentage change induced by combined insulin and iloprost infusion in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%